Regulation of gap junction coupling in bovine ciliary epithelium - Wang, Zhao (American Physiological Society, 2010)
Aqueous humor is formed by fluid transfer from the ciliary stroma sequentially across the pigmented ciliary epithelial (PE) cells, gap junctions, and nonpigmented ciliary epithelial (NPE) cells. Which connexins (Cx) contribute to PE-NPE gap junctional formation appears species specific. We tested whether small interfering RNA (siRNA) against Cx43 (siCx43) affects bovine PE-NPE communication and whether cAMP affects communication. Native bovine ciliary epithelial cells were studied by dual-cell patch clamping, Lucifer Yellow (LY) transfer, quantitative polymerase chain reaction with reverse transcription (qRT-PCR), and Western immunoblot. qRT-PCR revealed at least 100-fold greater expression for Cx43 than Cx40. siCx43 knocked down target mRNA expression by 55 ± 7% after 24 h, compared with nontargeting control siRNA (NTC1) transfection. After 48 h, siCx43 reduced Cx43 protein expression and LY transfer. The ratio of fluorescence intensity (R(f)) in recipient to donor cell was 0.47 ± 0.09 (n = 11) 10 min after whole cell patch formation in couplets transfected with NTC1. siCx43 decreased R(f) by ∼60% to 0.20 ± 0.07 (n = 13, P < 0.02). Dibutyryl-cAMP (500 μM) also reduced LY dye transfer by ∼60%, reducing R(f) from 0.41 ± 0.05 (n = 15) to 0.17 ± 0.05 (n = 20) after 10 min. Junctional currents were lowered by ∼50% (n = 6) after 10-min perfusion with 500 μM dibutyryl-cAMP (n = 6); thereafter, heptanol abolished the currents (n = 5). Preincubation with the PKA inhibitor H-89 (2 μM) prevented cAMP-triggered current reduction (n = 6). We conclude that 1) Cx43, but not Cx40, is a major functional component of bovine PE-NPE gap junctions; and 2) under certain conditions, cAMP may act through PKA to inhibit bovine PE-NPE gap junctional communication.